Trifolium L. from mountain Dagestan - A. D. Habibov; A. A. Habibov (Юг России: экология, развитие, 2015)
Comparative analysis of three ecological factors influence on changeability of generative sprout dry mass features in general and its components (leaves, stalks and floscule) hast been accomplished at the beginning phase of flowering of four species of clover: Trifolium ambiguum, T. medium, T. pratense and T. raddeanum of mountainous Daghestan. Structure influence of these factors on generative sprout weight features has been found. Maximum of the floscule dry mass is observed in Daghestan high mountain endemic T. raddeanum. Increase of the dry mass of the floscule in the sprout mass in general and of the main factor of the adaptive strategy Re with the height gradient growth are observed both at population and species levels.